SAT-LB117 POEMS Syndrome: Rare Presentation of New Onset Diabetes Mellitus - Jamal, Issra (J Endocr Soc, 2020)
Background: POEMS syndrome (Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal protein, Skin changes) is characterized by the presence of a monoclonal plasma cell disorder, peripheral neuropathy, and one or more of the following features: osteosclerotic myeloma, Castleman disease, increased levels of serum vascular endothelial growth factor (VEGF), organomegaly, endocrinopathy, edema, typical skin changes, and papilledema. Clinical Case: 45 year old male with no chronic medical issues presented initially to the orthopedic clinic with right hip pain, pelvic MRI showed a right iliac crest lesion. CT Guided biopsy was done and showed plasmacytoma. SPEP showed elevated IgG lambda level in the gamma zone. In the meantime he was complaining of ascending numbness and weakness in hands and feet and he progressively became wheelchair bound. During his treatment and follow ups with Hematology/Oncology he was noted to have elevated blood sugars in the 500s. Hemoglobin A1C was elevated at 9.5 which confirmed the diagnosis of new onset diabetes. He was also noted to have splenomegaly which confirmed the diagnosis of POEMS syndrome. He was started on insulin and he managed to achieve good diabetes control with insulin and dietary changes. He is currently status post stem cell transplantation with a good response and the weakness and polyneuropathy improved with PT and OT. POEMS syndrome has major and minor criteria for diagnosis, mandatory major criteria includes polyneuropathy, monoclonal plasma cell proliferative disorder (almost always lambda). Additional major criteria are sclerotic bone disease, castleman disease, elevated VEGF. Minor criteria are organomegaly, extravascular volume load, endocrinopathy, and skin changes. In order to diagnose the syndrome, mandatory major criteria, and one major and one minor criteria need to be clinically present. Endocrinopathy includes the adrenal, pituitary, thyroid, gonadal, parathyroid, and pancreatic glands. Two-thirds of patients had at least one endocrine abnormality at presentation. Endocrine abnormalities can also develop later, during the course of the disease. Hypogonadism is the most common endocrine abnormality. Elevated levels of follicle stimulating hormone in the absence of primary hypogonadism levels have been reported, hence history and physical examination is crucial to detect the development of endocrinopathies in POEMS syndrome. There are no current guidelines or recommendations about the frequency of screening for endocrinopathies but it is suggested to obtain a baseline of thyroid function test, pituitary, gonadal, and adrenal axis. In addition to baseline parathyroid hormone level, close monitoring of calcium and blood glucose levels once the diagnosis is confirmed in patients with suggestive symptoms. Conclusion: POEMS syndrome is a rare condition that involves multiple endocrine organs, currently there are no guidelines or recommendations to obtain baseline endocrine labs once the diagnosis is confirmed, but it might be appropriate if there is a high clinical suspicion. References: 1. Castillo JJ (2016). “Plasma Cell Disorders”. Primary Care.43(4): 677-691. doi:10.1016/j.pop.2016.07.002. PMID 27866585. 2. Warsame R, Yanamandra U, Kapoor P (2017). “POEMS Syndrome: an Enigma”. Current Hematologic Malignancy Reports.12(2): 85-95. doi:10.1007/s11899-017-0367-0. PMID 28299525. 3. Dispenzieri A (2017). “POEMS syndrome: 2017 Update on diagnosis, risk stratification, and management”. American Journal of Hematology.92(8): 814-829. doi:10.1002/ajh.24802. PMID 28699668. 4. Kaushik M, Pulido JS, Abreu R, Amselem L, Dispenzieri A (2011). “Ocular findings in patients with polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes syndrome”. Ophthalmology.118(4): 778-82. doi:10.1016/j.ophtha.2010.08.013. PMID 21035860.